Affiliative behaviour and conflictual communication during brief family therapy of patients with anorexia nervosa. - Karyn Doba; Laurent Pezard; Guillaume Berna; Jean Vignau; Jean-Louis Nandrino (PLoS ONE)
Objective Although patients with anorexia nervosa (AN) present positive responses to family therapy, the key features of therapeutic changes still require identification. This study explores the role of conflictual communication and affiliative nonverbal behaviour in therapeutic change in brief strategic family therapy (BSFT) for AN patients. Methods Ten female AN patients and their parents were included in the sample and took part in a 6-month follow-up of BSFT. The durations of conflictual communication and of affiliative nonverbal behaviour estimated by eye contact were compared between the first and the last sessions of family-based treatment using nonparametric statistical tests. Results An increase of the Body Mass Index associated with an increase in the conflictual communication expressed during BSFT sessions were observed. Moreover, affiliative nonverbal behaviour expressed by the father and the patient decrease, after a BSFT follow-up, in conflictual situations only. By contrast, no significant difference was observed in affiliative nonverbal behaviour expressed by the mother. Conclusion The present study demonstrates that the impact of the BSFT differs between members of a family: the AN patient and the father have established a new form of emotional functioning with a decrease in emotional involvement. The study of the combination between verbal and nonverbal communication can represent an important step in the understanding of the mechanisms of therapeutic change.